Zootaxa 5000: dates and frequencies of publications with notes on monographs and special collections - Zhang, Zhi-Qiang (Zootaxa, 2021)
On the occasion of the 5000th volume of Zootaxa, I herein provide the publication dates, page numbers and frequencies of all volumes/issues published in Zootaxa in one publication. The growth and development of Zootaxa are divided into three periods. The First Period (Explosive Growth) covers the first four years (Zootaxa 1 to 1,000) when each paper was separately issued; 67 monographs were published during this period.  The Second Period (Transformation) includes over seven years and a half from Zootaxa 1,001 to the last volume of 2012 (2,598 issues in total) when two or more papers were included in the same volume of 60 pages or more; 538 monographs of 60 pages or more and 16 special volumes (collections of papers) were separately issued as before. The Third Period (Sustainable Development) started from the first volume in 2013 when two or more issues were included in the same volume of 600 pages; 2,740 issues were published; 926 monographs and 29 special volumes were separately issued as before.